ЗАМОНАВИЙ ДАРСЛИКЛАРДА МУАММОЛИ ВАЗИЯТЛАРНИ БАЁН ЭТИШ ("Материаллар қаршилиги" ва "Техник механика" фанлари мисолида) - Набиев, А. (SCIENCE and SOCIETY, 2020)
The article outlines the importance of designing a new generation of textbooks, translating texts, translating educational objectives into tasks, and ensuring teacher-student collaboration.
Keywords: modular education; problem education; didactics; text; competence; interactivity; design; epyura